Generic stability of the spectra for bounded linear operators on Banach spaces. (1999) - Qun, Luo
Abstract : In this paper, we study the stability of the spectra of bounded linear operators B ( X ) in a Banach space X, and obtain that their spectra are stable on a dense residual subset of B ( X ) .